Small Cell Carcinoma of the Anal Canal: A Case Report and Review of Management Challenges - N V, Vinin; Murugavel, Hareni; Yahiya, Nabeel; Samuel, Seena Tresa; Aravind, Sithara; Jones, Joneetha; Muttath, Geetha (Asian Pacific Journal of Cancer Care, 2024)
Extrapulmonary small cell carcinoma (EPSCC) is an uncommon malignancy, with anal canal involvement being exceptionally rare. Here, we report a case of a 63-year-old HIV-positive male presenting with small cell carcinoma of the anal canal. The case highlights the diagnostic and management challenges associated with this aggressive tumor, particularly given the limited literature and the lack of clear treatment guidelines. The patient’s presentation, treatment course, and the unique considerations are discussed in this case report.